Patriarch Dioscorus of Alexandria. The Last Pharaoh and Ecclesiastical Politics in the Later Roman Empire. By Volker L. Menze. Oxford Early Christian Studies. Oxford: Oxford University Press, 2023. xii + 226 pp. $ 90.00 hardcover - Mikhail, Maged S. A. (Church history, 2024)
Patriarch Dioscorus of Alexandria. The Last Pharaoh and Ecclesiastical Politics in the Later Roman Empire. By Volker L. Menze. Oxford Early Christian Studies. Oxford: Oxford University Press, 2023. xii + 226 pp. $ 90.00 hardcover. - Volume 93 Issue 3.